2014
DOI: 10.1002/2014gl060450
|View full text |Cite
|
Sign up to set email alerts
|

Kelvin-Helmholtz unstable magnetotail flow channels: Deceleration and radiation of MHD waves

Abstract: The Kelvin-Helmholtz instability (KHI) of magnetotail flow channels associated with bursty bulk flows (BBFs) is investigated. MHD oscillations of the channel in both kink and sausage modes are investigated for KHI, and both the primary and secondary KHIs are found that drive MHD waves. These instabilities are likely to be important for flow channel braking where the KHI removes energy from the flow. At flow speeds above the peak growth rate, the MHD modes excited by KHI develop from surface modes into propagat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 18 publications
(46 reference statements)
4
20
0
Order By: Relevance
“…Cécere et al [] investigated numerically the occurrence of the KHI on the boundaries of SADs but did not investigate the possibility of the KH‐driven modes generating the emission of propagating fast magnetosonic modes. Similar to the breaking of BBFs suggested in Turkakin et al [], propagating wave emission due to the KHI along SAD boundaries may be possible and can potentially explain observed deceleration of SADs. Coronal plumes and coronal streamer boundaries have similar characteristics to SADs [ Andries and Goossens , ; Feng et al , ] and can thus support MHD wave emission as well.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Cécere et al [] investigated numerically the occurrence of the KHI on the boundaries of SADs but did not investigate the possibility of the KH‐driven modes generating the emission of propagating fast magnetosonic modes. Similar to the breaking of BBFs suggested in Turkakin et al [], propagating wave emission due to the KHI along SAD boundaries may be possible and can potentially explain observed deceleration of SADs. Coronal plumes and coronal streamer boundaries have similar characteristics to SADs [ Andries and Goossens , ; Feng et al , ] and can thus support MHD wave emission as well.…”
Section: Resultssupporting
confidence: 70%
“…Some studies have assumed a zero thickness boundary, which is appropriate if the wavelengths of the generated waves are significantly larger than the thickness of the boundary [ Pu and Kivelson , ; Mann et al , ; Turkakin et al , , ]. The effects of a finite boundary thickness have also been investigated in several studies [ Ong and Roderick , ; Walker , ; Farrugia et al , ; Contin et al , ; Gratton et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…A continuous deceleration of flow bursts along their propagation toward Earth has already been suggested in the above statistical investigations [Baumjohann et al, 1990;Shiokawa et al, 1997]; however, what mechanisms are causing this flow braking is not fully understood. For example, it has been suggested that the growth of Kelvin-Helmholtz waves on the boundary of flow channels can be important for flow braking in the magnetotail [Volwerk et al, 2007;Turkakin et al, 2014]. In this article we will instead investigate the possibility that compressed magnetic flux tubes in DFs can constitute local impediments to flow bursts along their earthward propagation.…”
Section: Introductionmentioning
confidence: 99%
“…The dipolarization front (e.g., Schmid et al, 2015Schmid et al, , 2016Sergeev et al, 2009), signed by the sharp enhanced Bz, has been proposed to be the possibly mechanism to decelerate the BBF (Hamrin et al, 2014). Another mechanism is the dissipation of the BBF kinetic energy by emitting KAW (e.g., Angelopoulos et al, 2002;Chaston et al, 2012;Higashimori & Hoshino, 2015;Turkakin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%